(untitled) (Conferencea, 2022)
This article provides data on effect of phosphorous application on leaf size of stevia plant. Accordingly, phosphorus feeding has been found to have a certain effect on the size of leaves, whether the leaves are large or small, and the width and length of each leaf in the stevia plant. In order to ensure that the size of the leaves of the stevia plant is large and fully meets the requirements of the model, it is recommended to meet the plant’s need for mineral nutrients, including phosphorus nutrients, during the season.